Analysis of vibration characteristic for helical gear under hydrodynamic conditions. (January 2017) - Liu, Fuhao; Jiang, Hanjun; Zhang, Liang; Chen, Li
Based on the elasto-hydrodynamic lubrication theory, a 2-degree-of-freedom nonlinear dynamic model of helical gears with double-sided film is proposed, in which the minimum film thickness behaves as a function of load parameters, lubricant parameters, and the geometry of the contact. Then, the comparison of the hysteresis loops in different gear models shows the soundness of the presented model. Using numerical method, the time evolution of lubricant normal force, minimum film thickness, and lubricant stiffness is obtained in order to demonstrate the influence of the driving torque and pinion's velocity. The results obtained in this article can contribute to the root cause for the gear vibration and show that the hydrodynamic flank friction has almost no influence on the gear system.